2015
DOI: 10.1016/j.orgel.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Fluorene bilayer for polymer organic light-emitting diode using efficient ionization method for atomized droplet

Abstract: a b s t r a c tWe present a solution-processed planar fluorene bilayer by an ultrasonic atomized deposition method in combination with a needle electrode as an ionization part for an atomized droplet. An important advantage of our method is that the atomized droplet is efficiently charged using a needle electrode, which speeds up the deposition rate of the polymer thin film. The deposition rate increases 2 to 3 times compared to a that obtained with a conventional technique without using the ionization method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The spray coated films show a large amount of ripples at the surface. Ripples induced by spray coating are mainly due to the complicated flow behavior in the liquid layer, which is widely reported in the literature. In the present study, the situation is complicated due to the used multicomponent solution. Having the substrate at elevated temperature causes a fast evaporation of the residual solvent during spray deposition and thereby limits the probability of equilibrating height difference via a vertical flow on the substrate.…”
Section: Resultsmentioning
confidence: 77%
“…The spray coated films show a large amount of ripples at the surface. Ripples induced by spray coating are mainly due to the complicated flow behavior in the liquid layer, which is widely reported in the literature. In the present study, the situation is complicated due to the used multicomponent solution. Having the substrate at elevated temperature causes a fast evaporation of the residual solvent during spray deposition and thereby limits the probability of equilibrating height difference via a vertical flow on the substrate.…”
Section: Resultsmentioning
confidence: 77%
“…We note that the achieved efficiency values (i.e., LE equal to 7.30 cd A –1 for ZnTPP-cc-gly 2 -modified OLED) are among the highest ever reported for similar OLED configurations (i.e., with a conventional architecture using a 70 nm thick F8BT EML and an Al cathode). For instance, when using an ultrathin LiF cathode interlayer or a Ca cathode, luminous efficiencies of the order of 7.0 cd A –1 have also been reported. It is worth noting, however, that Friend et al have previously reported that optimized OLEDs with an inverted configuration can be made to exhibit LEs of more than 20 cd A –1 by controlling the width of the recombination zone with an approximately 1 μm-thick F8BT layer and a zinc oxide/barium hydroxide electron injection/transport layer deposited at the bottom cathode contact …”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonic spray coating (USC) process, which is a new deposition technology that has high material utilization, may be an alternative for solution-processed OLEDs, especially in large-scale industrial production. The application of USC process in polymer LEDs (PLEDs), organic photovoltaic cells (OPVCs), and organic thin-film transistors (OTFTs) has been demonstrated. However, the USC process is still not generally recognized as an efficient solution process for OLEDs. During the USC process, a uniform liquid layer is necessary to form continuous organic thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, excess solution in the liquid layer could be obviously affected by its surface tension, and its complicated flow behavior, especially capillary flow, could not be ignored during the solvent evaporation. Finally, many ripples (coffee rings) occur in the formed organic film, leading to inhomogeneous film morphology. Since the thickness of conventional OLEDs is only about a hundred nanometers, the existence of ripples in films is very harmful for the application of these films in delicate OLEDs. To solve the problem, Girotto and co-workers have taken advantage of surface tension gradients to create Marangoni flows that enhance the coverage of the substrate and reduce the roughness of the film .…”
Section: Introductionmentioning
confidence: 99%